Acknowledgment to Reviewers of Journal of Functional Morphology and Kinesiology in 2021 - Journal of Functional Morphology Kinesiology Editorial Office (Journal of Functional Morphology and Kinesiology, 2022)
Rigorous peer-reviews are the basis of high-quality academic publishing [...]